Research of Translating's Categories of Thai Cuisine Names to Chinese - Chuensabai, Worayot; Makpun, Wadcharobon; Wanting, Huang (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2020)
Abstract The purpose of research that is for collecting, classifying and analyzing the translating of Thai cuisine names to Chinese from different sources such as books, website and menu. To classify Thai cuisine names to Chinese, it is based on three strategies of translation. First, it is "Literal translation strategy". Second is "Free translation strategy" and last one is "Transcription of translation strategy". The samples of this research is classified into 2 main types; First main type is "Meat Dish", it consists with 6 types. 1.184 names of curry dishes 2. 99 names of fried and stir-fried dishes 3. 51 names of salad dishes 4. 80 names of deep-fried and grilled dishes 5.30 names of dipping 6. 20 names of side dishes Second main type is dessert, 63 names is used as sample. After collecting all Thai cuisine names, they are brought to study, analyze the meaning and classify the names as following strategies. The result of research is calculated the average from total Thai cuisine names. There are 511 names that are analyzed as samples with non-duplicated translating. Most of samples are translated from Thai to Chinese language by using "Literal translation strategy". They are 55 percent of the total. Free translation strategy is used 42 percent of the Thai cuisine names. At least, Transcription of translation strategy is used only 3 percent of the total. There are 16 Thai names and 35 Chinese names that are analyzed as samples with duplicate translation. 66 percent of them are translated by using "Free translation strategy", 23 percent of them are translated by using "Literal translation strategy". At least, 11 percent of them are translted by using "Transcription of translation strategy"